2006
DOI: 10.1007/s00464-005-0409-x
|View full text |Cite
|
Sign up to set email alerts
|

Total and subtotal laparoscopic gastrectomy for adenocarcinoma

Abstract: Short-term results with laparoscopic gastrectomy were better than with open surgery in this study. Oncologic radicality was a major concern, but in the authors' experience the extent of lymphadenectomy was the same as in open surgery. This study suggests that laparoscopic gastrectomy in malignancies is a reliable tool and oncologic requirements can be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 33 publications
9
108
3
1
Order By: Relevance
“…In a randomized trial, Huscher et al [21] reported mortality and [29,30]. The mortality and morbidity rates in the current study were 0 and 4%, respectively, and less than those observed in our historical series of open surgeries.…”
Section: Discussioncontrasting
confidence: 65%
“…In a randomized trial, Huscher et al [21] reported mortality and [29,30]. The mortality and morbidity rates in the current study were 0 and 4%, respectively, and less than those observed in our historical series of open surgeries.…”
Section: Discussioncontrasting
confidence: 65%
“…Francescutti and colleagues 27 have reported the only previous Canadian experience, but they included patients with benign lesions as well as those with malignant ones. All comparative studies have reported decreased or similar early postoperative morbidity with LAG ranging from 0% to 26%, [15][16][17][26][27][28][29]31 which compares with our results. Other benefits of the laparoscopic ap proach, including decreased time to ambulation and resumed diet, decreased consumption of analgesia and a shorter length of stay, have been reported in these studies.…”
Section: Discussionsupporting
confidence: 88%
“…Others reported no difference between the laparoscopic and open approaches. 15,16,[26][27][28][29][30][31]33 In a meta-analysis of RCTs comparing laparoscopic and open approaches for early gastric cancer, Ohtani and colleagues 9 concluded that there was a lesser number of LNs with laparoscopy. Debate is still ongoing about the extent of the lymphadenectomy and the number of LNs needed in the specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading the full texts of the remaining papers, 24 studies were removed as they only reported the outcomes of LG for AGC whereas no controlled or matched cases treated by OG were available. Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63].…”
Section: Resultsmentioning
confidence: 99%